2002
DOI: 10.1074/jbc.m207398200
|View full text |Cite
|
Sign up to set email alerts
|

The Aes Protein and the Monomeric α-Galactosidase fromEscherichia coli Form a Non-covalent Complex

Abstract: Aes, a 36-kDa acetylesterase from Escherichia coli, belongs to the hormone-sensitive lipase family, and it is involved in the regulation of MalT, the transcriptional activator of the maltose regulon. The activity of MalT is depressed through a direct protein-protein interaction with Aes. Although the effect is clear-cut, the meaning of this interaction and the conditions that trigger it still remain elusive. To perform a comparative thermodynamic study between the mesophilic Aes protein and two homologous ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
17
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 31 publications
(44 reference statements)
6
17
0
Order By: Relevance
“…In a previous report [5] we confirmed the kinetic parameters of the acetyl-esterase Aes, obtained from Kanaya et al [2], at 25 °C and using pNP-butanoate as substrate. Because a complete biochemical characterization of Aes has never been reported we seek to fill this gap.…”
Section: Thermophilicity and Thermostabilitysupporting
confidence: 89%
See 2 more Smart Citations
“…In a previous report [5] we confirmed the kinetic parameters of the acetyl-esterase Aes, obtained from Kanaya et al [2], at 25 °C and using pNP-butanoate as substrate. Because a complete biochemical characterization of Aes has never been reported we seek to fill this gap.…”
Section: Thermophilicity and Thermostabilitysupporting
confidence: 89%
“…In fact it has been demonstrated that Aes negatively controls the activity of MalT, the transcriptional activator of the maltose regulon, by a direct protein-protein interaction [4]. Our group recently suggested a similar potential role of Aes in the regulation of the raffinose regulon via a specific protein-protein interaction with -galactosidase [5]. However, the physiological role of Aes in E. coli is still unknown; insertion mutations in aes gene do not result in any easily discernable phenotype and it has been reported that the basal level of Aes expression is very low [1].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…On the other hand, Mandrich, Caputo, Martin, Rossi, and Manco (2002) reported that the activity of the E. coli Aes protein, a carboxylesterase, increases six-fold when it binds to a 50 kDa a-galactosidase produced by the same bacterium. In this case the activating effect is due to a protein-protein interaction.…”
Section: Article In Pressmentioning
confidence: 96%
“…These papers mainly describe the use of the ProteinChip Arrays with purified proteins [10][11][12][13][14], or extracted surface proteins [15][16][17][18][19]. A few reports are available in the literature in which this technology is used with protein extracts [20][21][22].…”
mentioning
confidence: 99%